The Pico de Navas slump (Burgos, Spain): a large rocky landslide caused by underlying clayey sand fluidification - Sanz-Pérez, Eugenio; Menéndez-Pidal, Ignacio; Lomoschitz, Alejandro; Galindo-Aires, Rubén Ángel (Journal of Iberian Geology, 2016)
The Pico de Navas landslide was a large-magnitude rotational movement, affecting 50x106m3 of hard to soft rocks. The objectives of this study were: (1) to characterize the landslide in terms of geology, geomorphological features and geotechnical parameters; and (2) to obtain an adequate geomechanical model to comprehensively explain its rupture, considering topographic, hydro-geological and geomechanical conditions. The rupture surface crossed, from top to bottom: (a) more than 200 m of limestone and clay units of the Upper Cretaceous, affected by faults; and (b) the Albian unit of Utrillas facies composed of silty sand with clay (Kaolinite) of the Lower Cretaceous. This sand played an important role in the basal failure of the slide due to the influence of fine particles (silt and clay), which comprised on average more than 70% of the sand, and the high content presence of kaolinite (>40%) in some beds. Its geotechnical parameters are: unit weight (δ) = 19-23 KN/m3; friction angle (φ) = 13º-38º and cohesion (c) = 10-48 KN/m2. Its microstructure consists of accumulations of kaolinite crystals stuck to terrigenous grains, making clayey peds. We hypothesize that the presence of these aggregates was the internal cause of fluidification of this layer once wet. Besides the faulted structure of the massif, other conditioning factors of the movement were: the large load of the upper limestone layers; high water table levels; high water pore pressure; and the loss of strength due to wet conditions. The 3D simulation of the stability conditions concurs with our hypothesis. The landslide occurred in the Recent or Middle Holocene, certainly before at least 500 BC and possibly during a wet climate period. Today, it appears to be inactive. This study helps to understand the frequent slope instabilities all along the Iberian Range when facies Utrillas is present.